Insulation capability of the bark of trees with different fire adaptation - Bauer, Georg; Speck, Thomas; Blömer, Jan; Bertling, Jürgen; Speck, Olga (Journal of Materials Science, 2010)
When exposed to a surface ﬁre, the probability of a tree to survive widely varies, depending on its capability to protect the cambium from lethal temperatures above 60 C. Thereby, the bark, the entirety of all tissues outside the cambium, serves as an insulation layer. In laboratory experiments, the heat production of a surface ﬁre was simulated and the time span s60 until the temperature of 60 C is reached in the inner bark surface was measured. Thereby, s60—as a measure of the ﬁre resistance—was quantitatively determined for seven tree species. In addition, the inﬂuence of bark thickness and moisture content on bark heat insulation capacities was examined. Independent of the tree species and bark moisture content a power function correlation between bark thickness and s60 was found. Our results also show that ﬁre resistance increases with decreasing bark density. The seven tree species examined can be classiﬁed in two groups differing highly signiﬁcant in their bark structure: (1) tree species with a faintly structured bark, which show a low ﬁre resistance, and (2) tree species with an intensely structured bark, showing a high ﬁre resistance. Furthermore a mathematical model simulating heat conduction was applied to describe the experimental results, and some ideas for a transfer into biomimetic materials are presented.
Keywords: bark moisture; bark structure; bark thickness; fire resistance (voyant); surface fires